(untitled) (Manabia: Journal of Constitutional Law, 2025)
This article aims to discuss the application of immutable primsiple in Article 1 paragraph 1 of the 1945 Constitution to the Unitary State of the Republic of Indonesia using normative juridical research method and is analyzed using Hans Kelsen’s Stufenbau theory. This principle, in the context of a state of state, refers to certain concepts or elements that are considered unchangeable to ensure stability, continuity, and justice, often applied to fundamental aspects such as the constitution, Human Rights, the form of the state, and sovereignty. To maintain the integrity of the Unitary State of the Republic of Indonesia, irreversible rules are needed that concern several concepts that are considered unchangeable. clauses that cannot be changed in the 1945 Constitution article 1 paragraph 1 and article 37 paragraph 5 which discuss the nature of the state. This clause is important because it maintains the identity of constitutional principles, including state doctrine such as Pancasila and Bhinneka Tunggal Ika that is considered to originate from Indonesia, which is closely related to the constitutional state. To some extent, these immutable clauses guarantee the stability of the constitution as well as describe or imply the importance of the constitution as an important representation of the state. Furthermore, they demonstrate the state’s desire to remain faithful to the fundamental principles that form the constitusional identity. Efforts to safeguard the Unitary State of the Republic of Indonesia must be supported by promoting nationalism, patriotism, and the development of multicultural education.